3D Printing Technologies : Digital Manufacturing, Artificial Intelligence, Industry 4.0 - Anand, Satyajit; Anand, Sourabh; Bharti, Pushpendra S.; Bin Abu Bakar, Muhammad Umar Azizi; Boopathi, S.; Boopathi, Sampath; Chaitanya; Dixit, Amit Rai; Dubey, Abhishek; Dwivedi, Yashi; Goyal, Gulshan; Gupta, Arjun; et al. (De Gruyter, 2024)
Additive Manufacturing is a method of manufacturing parts and products directly from design data, by adding layers of materials in order to obtain the final shape and size with high accuracy and negligible waste. The book covers the latest developments of hybrid and bio-inspired 3D Printing, the use of Artificial Intelligence and the applications to Industry 4.0, real-time defect detection, hybrid and bio-inspired 3D Printing. .